EFFECT OF LIQUID NITROGEN FERTILIZER AND TIME OF APPLICATION ON THE GROWTH AND YIELD OF SORGHUM IN BAUCHI STATE, NIGERIA - Adamu, M. K.; Shuaibu, Y. M.; Fagam, A. S.; Kawure, S. (Nigerian Journal of Agriculture and Agricultural Technology, 2023)
Field experiment was conducted to study the effect of foliar nitrogen fertilizer and time of application on the growth and yield of sorghum at Student’s Demonstration Farm of the Bauchi State Collage of Agriculture, during the rainy season of 2018 and 2019. The treatments consisted of four rates of foliar nitrogen fertilizer (0, 1, 2 and 3 L/ha) and three times of application (once, twice and thrice). These were factorially combined to give 12 treatment combination and laid out in a Randomized Complete Block Design (RCBD) with three replications. Data were collected on plant height, number of leaves, leaf area, 1000 grain weight and grain yield. Data collected during the experiment were subjected to analysis of variance (ANOVA) and Duncan’s Multiple Range Test (DMRT) was adopted in separating the means. Results of the experiment indicated that, growing of sorghum using foliar nitrogen fertilizer with different times of application had significant (P≤0.05) effect on all the characters measured. It was further revealed that, application of foliar nitrogen fertilizer at rate of 1, 2 and 3 L/ha significantly (P≤0.05) influenced the growth and yield of sorghum better than the control. The result further revealed that, application of liquid nitrogen fertilizer twice and thrice significantly (P≤0.05) promoted growth and yield of sorghum and proved to be better than applying once. Based on the result of this study, growing sorghum with the application of foliar nitrogen fertilizer at the rates of 1 to 2 L/ha two to three times promoted the growth and yield of sorghum and can be adopted by farmers in the study area for improved sorghum production.